BIOACTIVITY AND CLONING OF A NEW ANTIBACTERIAL LECTIN PROTEIN IN SPONGE Gelliodes sp. FROM BARANGLOMPO ISLAND IN SOUTH SULAWESI INDONESIA TERRESTRIAL - Hanapi Usman; Prastawa Budi; Ahyar Ahmad (Indonesian Journal of Chemistry, 2010)
A research on antibacterial bioactivity of protein fraction isolated from several species of sponges of Barang Lompo Island has been conducted. Pre-purification of protein using fractional method, showed maximum bioactivity with the inhibition zone of 26 mm to Salmonella typhy from sponge Gelliodes sp. with the saturation level of ammonium sulfate of 40-60%. Further purification of this fraction using column chromatography followed by protein sequencing, indicated that pure protein as lectin, and behaves as a single-band on SDS-PAGE with molecular weight of 21 kDa. Based on amino acids partial sequence, we cloned and sequencedcDNA encoding lectin protein.It consists of 552 nucleotides encoding 183 amino acid residues including a putative initiationMet. To obtain it in large amounts, the coding sequence of lectin was cloned into pGEX-2TK vector and expression as a lectin fusion protein in Escherichia coli. Recombinant lectin exhibited a similar antibacterial activity to the native lectin. The recombinant lectin had stronger antibacterial activity toward S. typhy and S. aureus (G+) with the diameters of inhibition zone were 16 mm and 17 mm, respectively. This research might provide significant results for the following research on the antibacterial action in molecular level of lectin protein from marine sponges.